RETINAL FEATURES PREDICTIVE OF PROGRESSIVE STAGE 4 RETINOPATHY OF PREMATURITY - HARTNETT, M. ELIZABETH (2004)
PURPOSE: To determine the retinal features predictive of progressive stage 4 retinopathy of prematurity (ROP) after laser treatment for threshold ROP. METHODS: Retrospective review of 72 eyes of 37 infants after laser treatment for threshold ROP between 1993 and 2002. Retinal features were abstracted from examinations made within 1 week of development of stage 4A ROP or 2 weeks after laser treatment in eyes with regressed threshold disease. Predictive features of progressive stage 4 ROP were determined using a generalized estimating equation model to account for within-subject variability. RESULTS: The generalized estimating equation showed that vitreous state, ridge elevation of six or more clock hours, and two or more quadrants of plus disease predicted progressive retinal detachment, whereas two or more quadrants of neovascularization did not. CONCLUSIONS: Progressive stage 4 ROP requiring surgical intervention was predicted by the absence of clear vitreous, ridge elevation of six or more clock hours, and two or more quadrants of plus disease, but not by neovascularization. These results may be useful in the management of eyes after laser treatment for threshold ROP.